The poplar ARGOS-LIKE gene promotes leaf initiation and cell expansion, and controls organ size - B. R. Kuluev; A. V. Knyazev; E. V. Mikhaylova; A. A. Ermoshin; Y. M. Nikonorov; A. V. Chemeris (Biologia Plantarum, 2016)
We identified a Populus nigra auxin-regulated gene involved in organ size (PnARGOS)-LIKE, encoding one organ size related protein in black poplar. It is homologous to AtARGOS and AtARGOS-LIKE genes of Arabidopsis thaliana. ABRE-like, G-box, GATA and I-box motifs were discovered in the promoter region of the poplar ARGOS-LIKE gene. In wild type aspen (Populus tremula) plants, an ortholog of the PnARGOS-LIKE gene (PtrARGOS-LIKE) was noticeably expressed in actively dividing and expanding young leaves and calli, whereas its mRNA content increased in response to exogenous 6-benzylaminopurine, 1-naphthaleneacetic acid, and 24-epibrassinolide. Expression of the PtrARGOS-LIKE gene was reduced under a salinity treatment. In addition, we generated transgenic tobacco and aspen plants with an up-regulated expression of the PnARGOS-LIKE gene. A constitutive expression of the gene contributed to an increase in size of stems and leaves of the transgenic tobacco plants. In the transgenic aspen, a constitutive expression of the PnARGOS-LIKE gene promoted an increase in the frequency of leaf initiations and in leaf length and area. The size of transgenic tobacco and aspen leaves increased due to the enlargement of individual cells. The results show the significance of the PnARGOS-LIKE gene for control of leaf initiation and organ growth by cell expansion in poplar.